Are Occupational Complexity and Socioeconomic Position Related to Psychological Distress 20 Years Later? - Darin-Mattsson, Alexander; Andel, Ross; Fors, Stefan; Kåreholt, Ingemar (Journal of aging and health, 2015)
OBJECTIVE: To assess occupational complexity in midlife in relation to psychological distress in older adulthood (69+ years) and explore the role of socioeconomic position. METHOD: Baseline data from the Swedish Level of Living Survey and follow-up data from the Swedish Longitudinal Study of Living Conditions of the Oldest Old were combined, resulting in 20+ years of follow-up. Data were analyzed using ordered logistic regressions. RESULTS: Higher occupational complexity was associated with less psychological distress 20 years later adjusted for age, sex, follow-up year, hours worked the year before baseline, and psychological distress at baseline. Higher socioeconomic position yielded the same pattern of results. Socioeconomic position partially accounted for the association between occupational complexity and psychological distress. DISCUSSION: With social gradient not easily amenable to modification, efforts to increase engagement at work may offer a viable option to attenuate the influence of work environment on psychological distress later in life.
Keywords: psychický stres; psychological distress; Occupations; old age; následné studie; lidé; Middle Aged; Švédsko; Female; Longitudinal Studies; population based; Humans; Sweden; Follow-Up Studies; lidé středního věku; mužské pohlaví; společenská třída; zaměstnání; ženské pohlaví; Stress, Psychological; Aged, 80 and over; senioři nad 80 let; longitudinální studie; Aged; Male; Social Class; socioeconomic position; occupational complexity; senioři